Adaptive Vibration Controller Design for Structural Systems Despite Unknown Seismic Disturbance - Kararsiz, Gokhan; Yazici, Hakan; Basturk, Halil Ibrahim; Guclu, Rahmi (IEEE, 2018)
This paper presents active vibration controller design for structures under the effect of unmeasured seismic earthquake disturbances. It is assumed that the disturbance consists of a sum of sinusoidal where amplitude, frequency and phase are unknown. Then, an observer is constructed for unmeasured disturbance with considering the assumptions. Then, an adaptive backstepping controller is designed for the actuator input. The stability of the closed loop system is proven and the effect of the seismic earthquake disturbance is mitigated. To reveal the success of the design, a simulation is prepared where the disturbance excites the natural frequencies of the structure.
Keywords: Automation & Control Systems